الفوز العظيم في القرآن الكريم: موجباته وثمراته - عيد، إسراء محمود (جامعة باتنه 1 - كلية العلوم الإسلامية, 2020)
الفوز بالجنة والنجاة من النار هو غاية كل مسلم، وهو الفوز العظيم الذي بينه الله في كتابه الحنيف، وجعل له أسباباً تقود إليه، سلطت الضوء في بحثي هذا على أهمها: كالإيمان بالله والعمل الصالح، والوقوف على حدوده، وطاعة الله ورسوله، والجهاد في سبيله، والأمر بالمعروف والنهي عن المنكر، وإقامة الصلاة وإيتاء الزكاة، وسداد القول وصلاحه، كما بينت ثمرات الفوز العظيم ونتائجه ومن أهمها: دخول جنات تجري من تحتها الأنهار والخلود فيها، ونيل رضوان الله تعالى، والرؤيا الصالحة، والبشارة عند الموت والبعث، وصلاح الأعمال ومغفرة الذنوب، وعدم الموت في الآخرة، والوقاية من السيئات، إضافة إلى النور الذي يضيء المؤمنين من أمامهم وأيمانهم، وهذا كله فضلاً من الله وكرماً منه سبحانه.
Winning paradise and escaping hellfire is the goal of every Muslim. It is the greatest victory that God has shown in his Holy Book and gave many reasons that lead to achieving this. In this research, I have highlighted the most important reasons such as believing in God, doing good deeds, adhering to His limits, obeying God and His Messenger, jihad in God’s path, promotion of virtue, prevention of vice, establishing prayer, paying zakat, and speaking good, valid words. I have also conveyed the great victor’s fruits and results, the most important of which are: entering paradise and remaining there for eternity, obtaining God’s satisfaction, good visions, good news at death and resurrection, increase in good deeds, forgiveness of sins, not dying in the afterlife, protection from bad deeds, in addition to the light that illuminates the believers’ path. This is all from God’s favor and generosity.
Keywords: القرآن الكريم -- الآيات القرآنية -- التفسيرات القرآنية -- الكتب الدينية